2019
DOI: 10.14744/nci.2019.22697
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low and high dose empagliflozin on HbA1c and lipid profile in Type 2 Diabetes mellitus: A real world data

Abstract: M etformin is the classical first-line treatment to provide glycemic control in patients with type 2 diabetes mellitus (T2DM). However, metformin alone may usually not sustain glycemic control for a long time [1], and additional treatments are needed in most patients [2]. Although they seem to be effective at first, sulfony-lureas and oral hypoglycemic agents are difficult to tolerate due to the side effects [3]. Therefore, patients with T2DM need effective and well-tolerated new antidiabetic agents that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, the effect of SGLT2 inhibitors on blood lipids remains unclear. There were a number of studies or meta-analyses that tried to explore, but the conclusions were not identical [10][11][12][13][14][15][16][17]. Some studies shown that SGLT2 inhibitors do not affect lipid metabolism, and there is no signi cant difference in lipid pro le before and after SGLT2 inhibitors treatment [14,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effect of SGLT2 inhibitors on blood lipids remains unclear. There were a number of studies or meta-analyses that tried to explore, but the conclusions were not identical [10][11][12][13][14][15][16][17]. Some studies shown that SGLT2 inhibitors do not affect lipid metabolism, and there is no signi cant difference in lipid pro le before and after SGLT2 inhibitors treatment [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…There were a number of studies or meta-analyses that tried to explore, but the conclusions were not identical [10][11][12][13][14][15][16][17]. Some studies shown that SGLT2 inhibitors do not affect lipid metabolism, and there is no signi cant difference in lipid pro le before and after SGLT2 inhibitors treatment [14,16]. Others demonstrated that triglyceride levels dropped and total cholesterol, LDL-cholesterol, and HDL-cholesterol rose signi cantly when taking SGLT2 inhibitors [13,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitors enhance glycosuria by preventing glucose reabsorption in the kidney [ [15] , [16] , [17] ]. The impact of SGLT2 inhibitors on glucose metabolism in diabetic patients has been extensively studied [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. They reduced fasting blood glucose and glycated hemoglobin (HbA1c), and improved insulin sensitivity and β cell function in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid metabolism with SGLT2 inhibitor therapy has been also investigated, but the results are controversial. The inhibitors led to body weight loss, and reduced VAT and liver fat in diabetic patients [ [18] , [19] , [20] , [21] , [22] , 24 ]. The loss of blood glucose due to glycosuria is expected to increase glucagon secretion, which stimulates fatty acid oxidation and consequently reduces body fat content [ [25] , [26] , [27] ].…”
Section: Introductionmentioning
confidence: 99%